A content analysis on the representation of incumbent female senators in the Philippine Daily Inquirer, The Philippines Star, and Manila Bulletin - Lina, Odelinne Jan Pastorelo 1996-; Roxas, Stephanie Suan; Khan, Rachel E. (2018)
"This thesis examined the three top-tier broadsheets in the country namely Philippine Daily Inquirer, Philippine Star and Manila Bulletin on their coverage of the female senators during the first year of the Duterte administration. It seeks to answer the question if the media is gender-neutral or gender-biased on covering female senators. The theories used for this study are the framing theory and liberal feminism. For the methodology, the researchers used content analysis, and classified the media frame and gender lens present. The media ethical guidelines of the Philippine Commission on Women and the Magna Carta for Women were used to see if there were any ethical violations made. The qualitative data included interviews of the editors of the respective newspapers to further support the quantitative data at hand. The researchers found that although the coverage of the three broadsheets were dominantly neutral, there is still a small percentage of stereotypes and images that were present. Gender had no role in the coverage of the broadsheets. There was a lack of stories on female senators because of the inactivity of these politicians, and the media's role as a reporter and a relayer of information is only limited. Women is therefore called to be move involved in different social issues, and to be more vocal in defending of what they believe is right. This is for the women population to be represented, recognized and valued information is only limited. Women is therefore called to be more involved in different social issues, and to be more vocal in defending of what they believe is right. This is for the women population to be represented, recognized and valued."
Vita.
Thesis (A.B. Journalism)--University of the Philippines Diliman
Keywords: Women legislators -- Philippines -- Press coverage